Discovery of Eoperipatus sp. (Peripatidae), the first representative of Onychophora in Vietnam - Bai, Thai Tran; Anh, Nguyen Duc (Academia Journal of Biology, 2012)
﻿Eoperipatus sp. (Peripatidae), the first representative of Onychophora was recorded for the first time in Vietnam. The material was collected from Cat Tien national park in environs of Bau Sau forest station. The habitat is mixture of the monsoon tropical forest with predominance of Tetrameles and Lagerstroemia, with numerous volcanic tuff rocks and dense grass vegetation (ferns). The studied material was found under rocksin wet environment.The material is a male specimen, 39 mm in length, 4 mm in greatest breadth and 2 mm in greatest dorso-ventral diameter. Antennae with 2.2 mm in length, 0.75 mm in diameter on their base and 0.35 mm indiameter on their top.The dorsal surface of fixed specimen in alcohol is colored dark with a mid-dorsal line, which extends from the region of the first pair of legs nearly as far back as the anus. The ventral surface is pale with alternation of white spots on mid-ventral line: the orifices of ventral and preventable organs.There are 23 pairs of legs, with 4-5 spinouts pads. Feet with two distal papillae, one on the anterior and one on the posterior side. Nephridial openings of fourth legs are situated between the third and the fourth pads.Legs with well-developed coxal organs. The genital orifice is situated between the penultimate pair of legs.The discovery of the first representative of Onychophora in Vietnam not only provides a new data on distribution of this phylum, but also suggests several interesting researches on diverse domains of biology, for example: phylogeny of Bilateria, especially Articulata; biogeography; morphological and physiological adaptations to terrestrial environment.